Dragonfly Diversity in A Residential Environment - Astrid Sri Wahyuni Sumah; Maisya Zahra Al Banna (Jurnal Biologi Tropis, 2023)
Dragonflies (Ordo Odonata) are attractive and colorful insects in aquatic and wetland ecosystems. Dragonflies have large, transparent and long wings which make them one of the most agile flying insects. Dragonflies are also one of the insects that are often used as water quality indicators. This study was to determine the diversity of dragonflies in three types of habitats and their correlation with environmental factors. The research was conducted in a residential area in Palembang City in November 2022 using the scan sampling method. The total number of dragonflies found was 18 species and 538 individuals divided into 2 suborders and 4 families. Orthetrum sabina dragonfly is the dominant dragonfly species found (136 sp). Meanwhile, Ischnura verticalis, Pseudagrion microcephalum, Agriocnemis rubescens and Nosoticta sp. is the rarest species of dragonfly to be found. The diversity value of the Shannon-Wiener index indicates that dragonflies prefer open habitats. Habitat shape and plant vegetation affect the number of dragonflies found, but does not affect the abundance of these dragonflies. The results of the analysis show that wind speed and temperature affect the presence of dragonflies during the observation.